Results of varietal testing of peking cabbage with a repeated planting in Uzbekistan - Khurramov Ulugbek Kholmamatovich; Namozov Ikhtiyor Choriyevich; Bolikulova Shohzoda Nasimovna (Research Parks Publishing LLC, 2020)
Peking cabbage is widespread in the countries of South-East Asia. For Uzbekistan, it is a little-known culture. In connection with this, the variety testing of 8 hybrids and 2 varieties of this foreign selection culture was carried out. By results of researches it was revealed that hybrids Seo Jin F1and Monoko F1 are the most productive and early ripening.